Efficacy of biosynthesizing folate, riboflavin and typical probiotic traits reveal the potential use of \(Lactobacillus plantarum\) LCN13 as a feed additive for swine farming - Hanh Nguyen, Vu Thi; Ngoc Tung, Quach; Thi Lien, Bui; Huyen Trang, Nguyen; Van The, Nguyen; Thanh Loi, Nguyen Thi; Hoang Ha, Chu; Quyet Tien, Phi (Academia Journal of Biology, 2022)
Lactic acid bacteria have been advocated as probiotics to replace antibiotic growth promoters, improve growth performance, and reduce cost production in swine farming. The aim of this study is to identify and evaluate the probiotic traits of strain LCN13 isolated from traditionally fermented feed for swine. Thirty-five bacterial isolates with different morphological characteristics were isolated, among which 9 isolates showed the ability to produce lactic acid and antibacterial activity against pathogenic bacteria. Among them, isolate LCN13 exhibited a strong capacity to produce lactic acid (18.5 ± 0.31 g/L), inhibited gastrointestinal pathogens such as Salmonella typhimurium ATCC 14028 (18.3 ± 1.52 mm), Escherichia coli ATCC 11105 (24.7 ± 2.14 mm), and Staphylococcus epidermidis ATCC 35984 (31.6 ± 2.93 mm), and produced 182 ng/mL folate and 233 ng/mL riboflavin as measured by LC-MS/MS after 24 hours of incubation. Based on morphological, biochemical, and 16S rRNA gene analysis, the isolate LCN13 was identified as Lactobacillus plantarum. Phenotypic analysis revealed that L. plantarum LCN13 showed remarkable resistance to 1.2% ox-bile salt, 2.0 mM H2O2, and pH 3.0. In addition, the ability to produce high levels of folate (253.6 ± 10.7 ng/mL) and riboflavin (312.0 ± 12.2 ng/mL) after 48 hours was exploited for the first time in the L. plantarum. Taken together, L. plantarum LCN13 might serve as a potential probiotic candidate for animal farming.